2022
DOI: 10.1186/s12966-022-01248-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between infant movement behaviours and development

Abstract: Background This study aimed to address methodological limitations of the evidence that informed national and international movement behaviour guidelines for the early years. Specifically, the primary objective was to examine the longitudinal associations of infant physical activity (i.e., tummy time) and sedentary behaviour (i.e., back time, screen time, reading time, restrained time) with gross motor development. Secondary and tertiary objectives were to examine longitudinal associations of: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Conversely, parents reported that a large proportion of their children were meeting sleep guidelines, which was also one of parents’ key priorities. Levels reported here were comparable to those in a Canadian cohort [ 11 ], but higher than those in Australian children [ 15 ]. It is perhaps unsurprising that parents prioritise this behaviour, given sleep (or lack thereof) often has wide-ranging influences on physical and mental health of young families, particularly during the first years of life [ 17 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Conversely, parents reported that a large proportion of their children were meeting sleep guidelines, which was also one of parents’ key priorities. Levels reported here were comparable to those in a Canadian cohort [ 11 ], but higher than those in Australian children [ 15 ]. It is perhaps unsurprising that parents prioritise this behaviour, given sleep (or lack thereof) often has wide-ranging influences on physical and mental health of young families, particularly during the first years of life [ 17 ].…”
Section: Discussionsupporting
confidence: 75%
“…The results of our study contradict previous studies showing higher tummy time adherence at 4 month olds. A recent Canadian study showed children aged 2 and 6 months engaged in approximately 48 and 116 min/day of tummy time respectively, substantially more than the 31 min/day reported in this study [ 11 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…19,20 Finally, significant correlations with medium to large effect sizes (r s = .30-.56) were observed between the questionnaire measure and a 3-day time use diary measure of these movement behaviors across time points in a subsample of participants from the Early Movers project. 20,21 A more detailed description of the diary measures could be found elsewhere. 19…”
Section: Methodsmentioning
confidence: 99%